1998
DOI: 10.1091/mbc.9.6.1367
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rho Is Required for cAMP-induced Melanoma Cell Differentiation

Abstract: Up-regulation of the cAMP pathway by forskolin or ␣-melanocyte stimulating hormone induces melanocyte and melanoma cell differentiation characterized by stimulation of melanin synthesis and dendrite development. Here we show that forskolin-induced dendricity is associated to a disassembly of actin stress fibers. Since Rho controls actin organization, we studied the role of this guanosine triphosphate (GTP)-binding protein in cAMP-induced dendrite formation. Clostridium botulinum C3 exotransferase, which inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 37 publications
(41 reference statements)
3
72
1
1
Order By: Relevance
“…However, it has not yet been determined whether phosphatidylinositol 3-kinase links DCC to activation of Rac1 upon binding to netrin-1. Protein kinase A phosphorylation of RhoA and the intracellular level of cAMP negatively regulate the activity of RhoA in different cell types (41), and the inhibition of RhoA and of its effector, Rho kinase, is required for cAMP-induced outgrowth of dendrites in B16 cells (42). The effects shown here mediated by DCC may be a consequence of a coordinated activation of Rac1 leading to actin polymerization at the advancing edge of the growth cone and inactivation of RhoA through the maintenance of the intracellular levels of cAMP in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has not yet been determined whether phosphatidylinositol 3-kinase links DCC to activation of Rac1 upon binding to netrin-1. Protein kinase A phosphorylation of RhoA and the intracellular level of cAMP negatively regulate the activity of RhoA in different cell types (41), and the inhibition of RhoA and of its effector, Rho kinase, is required for cAMP-induced outgrowth of dendrites in B16 cells (42). The effects shown here mediated by DCC may be a consequence of a coordinated activation of Rac1 leading to actin polymerization at the advancing edge of the growth cone and inactivation of RhoA through the maintenance of the intracellular levels of cAMP in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inactivation of Rho could also be caused by cAMPmediated modulation of Rac activity. In this context, it was found that the cAMP-induced differentiation of melanoma cells is not only overcome by transfection of cells with constitutively active Rho, but also by transfection with constitutively active Rac (23). In any case, the direct target of cAMP in endothelial cells controlling Rho activity awaits further identification.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, inhibition of Rho by C3 transferase from Clostridium botulinum blocks endothelial contractility in the same manner as cAMP-elevating drugs (3,18). Moreover, cAMP-elevating agents and C3 transferase can in a similar way inhibit various Rho-mediated cell functions such as tyrosine phosphorylation of paxillin in murine Y1 adrenal cells (21), NK cell function (22), melanoma cell differentiation (23), and integrin receptor clustering (24). Furthermore, it was shown that cAMP-induced morphological changes of neuronal cells are counteracted by active Rho (25).…”
mentioning
confidence: 99%
“…In human melanocytes the balance between Rac and Rho activation is a strong determinant of melanocyte dendrite formation [14][15][16][17]. Other important determinants of cytoskeletal remodeling in human melanocytes are the protein kinase C (PKC) signaling pathway [18].…”
Section: Introductionmentioning
confidence: 99%